Pancreatic cancer in obstructive jaundice in unexpected age - Katay, Karmen Bahnam; Khamis, Reem Hamed; Al Safar, Thafar Salim (International Journal of Research in Medical Sciences, 2021)
Cancer of the pancreas is a highly lethal malignancy. It is considered as the fourth leading cause of cancer-related death in the United States and second only to colorectal cancer as a cause of digestive cancer-related death.It is hoped that detection of asymptomatic and early stage of disease is potentially curable pancreatic cancer and it will improve outcomes. Our case report is 45 years old female who presented at our primary health care centre with obstructive jaundice for only 2 weeks and no weight loss, vague abdominal pain. She had intermittent epigastric pain for past few months and diagnosed as gastroesophageal reflex. Also, she had chronic anemia and need blood transfusion in the past 3 years. No family history of pancreatic cancer and no other risk factor. Most articles reveal difficulty in diagnosing pancreatic cancer in early stage and young age group due to its resemblance to benign lesion. That’s why we prefer to do case report for documentation. Diagnosis of the tumor is important especially in early stages for improving prognosis.